2017
DOI: 10.1021/acs.analchem.7b00724
|View full text |Cite
|
Sign up to set email alerts
|

Measuring 15N Abundance and Concentration of Aqueous Nitrate, Nitrite, and Ammonium by Membrane Inlet Quadrupole Mass Spectrometry

Abstract: An automated sample preparation unit for inorganic nitrogen (SPIN) coupled to a membrane inlet quadrupole mass spectrometer (MIMS) was developed for automated and sensitive determination of the N abundances and concentrations of nitrate, nitrite, and ammonium in aqueous solutions without any sample preparation. The minimum N concentration for an accurate determination of theN abundance is 7 μmol/L for nitrite and nitrate, with a relative standard deviation (RSD) of repeated measurements of <1%, and 70 μmol/L w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…The extracts were analyzed colorimetrically for the concentrations of NO 3 − and NH 4 + using a San ++ continuous flow Analyzer (Skalar Analytical B.V., Breda, The Netherlands). 15 N concentration in NH 4 + and NO 3 − was analyzed using an automated sample preparation unit for inorganic nitrogen coupled to a membrane inlet quadrupole mass spectrometer (QMS, GAM 200, InProcess, Bremen, Germany) as described in detail by Eschenbach et al (2017Eschenbach et al ( , 2018. In parallel subsamples, soil water content was determined by oven drying at 105°C.…”
Section: Harvest and Analyses Of Plant And Soil Materialsmentioning
confidence: 99%
“…The extracts were analyzed colorimetrically for the concentrations of NO 3 − and NH 4 + using a San ++ continuous flow Analyzer (Skalar Analytical B.V., Breda, The Netherlands). 15 N concentration in NH 4 + and NO 3 − was analyzed using an automated sample preparation unit for inorganic nitrogen coupled to a membrane inlet quadrupole mass spectrometer (QMS, GAM 200, InProcess, Bremen, Germany) as described in detail by Eschenbach et al (2017Eschenbach et al ( , 2018. In parallel subsamples, soil water content was determined by oven drying at 105°C.…”
Section: Harvest and Analyses Of Plant And Soil Materialsmentioning
confidence: 99%
“…It has gained interest since it was first reported in 1987 [1] as it allows real-time analysis of water and air samples by mass spectrometry [2] and generally preconcentration of targeted compounds. Its use spans from detection of organics in water to the more recent analysis of nitrites and nitrates [3]. MIMS technology is based on the separation of the analyte stream and the mass spectrometer inlet by a membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We can exclude this difference being due to an N 2 blank, because this would lead to a linear relationship for the reciprocal sample amounts 19 . As it has been shown that the reaction yield is not affected by the sample/reagent ratio, 12 we speculate that the offset and amount dependency observed here could be a result of fractionation due incomplete gas transfer in the membrane inlet, with lower yields and thus increasing apparent fractionation for higher sample amounts.…”
Section: Discussionmentioning
confidence: 71%
“…While the setup has been specifically developed for the analysis of natural abundance samples, it can also be used for the analysis of labelled samples. For labelled samples, nitrite can also be analysed after conversion into nitrous monoxide (NO) by KI (see Eschenbach et al 12 ) while the NO + fragment ion that is produced from the N 2 O reference gas in the ion source can be used for referencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation